A review of the safety and efficacy data for insulin glargine 300 units/ml, a new formulation of insulin glargine. Issue 12 (10th September 2015) - Dailey, G.; Lavernia, F.
Abstract : Insulin glargine 100 units/ml (Gla‐100) has become a standard of care in diabetes treatment over the past decade, providing 24‐h basal insulin coverage after once‐daily subcutaneous injection for many people with diabetes, with a well‐established efficacy and safety profile. New insulin glargine 300 units/ml (Gla‐300) is a basal insulin that provides the same number of units as Gla‐100 in a third of the volume. Compared with Gla‐100, Gla‐300 has shown more constant and prolonged pharmacokinetic (PK)/pharmacodynamic (PD) profiles. This review summarizes the findings from the EDITION series of clinical trials that investigated Gla‐300 in individuals with type 1 and type 2 diabetes mellitus. Overall, Gla‐300 has been shown to achieve similar glycaemic control with less, or similar, nocturnal hypoglycaemia compared with Gla‐100, and a trend towards lower hypoglycaemia at any time of day. The EDITION series of clinical trials also provides some evidence for less weight gain with Gla‐300 than with Gla‐100. In addition, the PK/PD profiles of Gla‐300 may allow more flexibility in the timing of doses, improving convenience; thus, Gla‐300 could offer several positive features for individuals with diabetes requiring basal insulin therapy.